Agricultural homogeneous areas in the eastern of La Pampa province, Argentine (Semiárida, 2020)
The objective of this study was to delimitate areas with homogeneous agricultural production behavior in the eastem of La Pampa province (Argentina). Multivariate analysis (cluster and principal component analysis) was done using sunflower, com, sorghum and wheat departmental annual yieids during the period 1980-1997. Six areas were delimited which were composed by the following departments: 1) Chapaleufú, Marac6 and Quemú Quemú, 2) Conhelo, Rancul, Realic6, and Trenel, 3) Atreuco, Capital and Catriló, 4) Guatraché, Toay and Utracan, 5) Loventué and 6) Hucal. This distribution would be related to soils, geoforms and weather conditions. The areas with high productivity, for the considered crops, were located at the North and the East of the studied region.
Keywords: Agricultural zoning; sunflower; com; sorghum; wheat